2018
DOI: 10.4103/ijdr.ijdr_184_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vimentin and CD44 in mucoepidermoid carcinoma: A role in tumor growth

Abstract: Our results may disclose a definite relationship between microvessl density (MVD), VM, EMT, and CSCs in MEC samples. Thus, it is reasonable to suggest that CSCs are related to angiogenesis and VM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[ 51 ] Identifying the biomarkers of stem cells which acquire EMT characteristics may also improve the development of drugs targeting EMT CSCs. [ 52 53 54 55 ]…”
Section: Onclusionmentioning
confidence: 99%
“…[ 51 ] Identifying the biomarkers of stem cells which acquire EMT characteristics may also improve the development of drugs targeting EMT CSCs. [ 52 53 54 55 ]…”
Section: Onclusionmentioning
confidence: 99%
“…VM formation involves tumor growth and cancer metastasis and in OSCC, it is correlated to highgrade tumors. On the other hand, VM formation is correlated to tumor plasticity and CSCs, a small subpopulation of cells within tumors, which are capable of selfrenewal, differentiation, and tumorigenicity (8,26). Supporting documents indicate that in highly aggressive epithelial cancers, VM formation promotes the overexpression of the mesenchymal phenotype through EMT phenomenon, which converts immobile epithelial cells to migratory mesenchymal cells (5,44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the lower the differentiation level, the more abilities of cancer cell migration, invasion, and metastasis. In ad-dition, angiogenesis is critical for cancer progression and metastasis; hence, the number of vascular channels increases in cancer tissues to provide adequate nutrition for cancer cells (23,(25)(26)(27). Several molecules and signaling factors are involved in angiogenesis in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor initiation [9]. Enhancement of proliferation and migration, and apoptosis inhibition in HNC [106,115].…”
Section: Cell Surface Markers Cd44mentioning
confidence: 99%
“…Moreover, a combination of three cancer stem cell markers - CD44, CD133 and SOX2 - was suggested to be a powerful and practicable prognosticator for patients with MEC of minor salivary glands [ 138 ]. Additionally, there was a positive correlation between CD44 and vimentin (a marker of EMT) expression level, and the levels of both CD44 and vimentin are associated with MEC tumor grade [ 115 ]. A previous study has reported that suberoylanilide hydroxamic acid (SAHA), an inhibitor of histone deacetylases (HDACs), was capable of disrupting CSCs in MEC cell lines and sensitizing tumor cells to cisplatin treatment, emphasizing the role of MEC CSCs in the well-recognized resistance of salivary gland tumors to chemotherapy [ 139 ].…”
Section: Characterization Of Oral Non-scc Cancer Stem Cellsmentioning
confidence: 99%